Social Psychology / Second Edition - Hogg Michael A; Vaughan Graham M (Prentice Hall, 1998)
Preface and Acknowledgements, Foreword, Introduction, Social Cognition and Social Thinking, Causal Attribution and Social Knowledge, Nature and Measurement of Attributes, Changing Attitudes, Social Influence, Basic Group Processes, Leadership and Group Decision-Making, Prejudice, Intergroup Behaviour, Aggression, Affiliation and Attraction and Love, Prosocial BehaviourLanguage and Communication, The Physical Environment and Social Behaviour, Glossary, Reference, Author and Subject Index.